Atypical meningioma: progression-free survival in 161 cases treated at our institution with surgery versus surgery and radiotherapy - Masalha, Waseem; Heiland, Dieter Henrik; Franco, Pamela; Delev, Daniel; Haaker, Jan Gerrit; Schnell, Oliver; Scheiwe, Christian; Grauvogel, Juergen (Journal of Neuro-Oncology, 2018)
Although atypical meningioma recurs frequently in spite of total resection and/or radiotherapy, no consensus on optimal adjuvant management was found. However, several retrospective studies analysed the additional effect of adjuvant radiotherapy in atypical meningioma with inconsistent results. Therefrom, the purpose of this study was to evaluate prognostic factors influencing the recurrence/progression and progression-free survival (PFS) rates of atypical meningioma, particularly focused on the role of postoperative adjuvant radiotherapy. Between February 2001 and March 2015, 161 atypical meningioma resections were performed in our Department of Neurosurgery, of which, 128 cases underwent surgical treatment alone and 33 cases underwent surgery and radiotherapy. Kaplan–Meier analysis was used to provide median point estimates and PFS rates. The Cox-regression model was used in the univariate and multivariate analysis to identify significant factors associated with treatment. The extent of resection (Simpson grade I and II) significantly influenced the risk of recurrence (hazard ratio = 1.8, CI (95%) 1.3–2.6, p-value = 0.0004). There was no significant benefit for progression-free survival after adjuvant radiotherapy (hazard ratio = 1.48, CI (95%) 0.76–2.86, p-value = 0.22). Additionally, meningioma located at the anterior and posterior fossa showed a significantly longer PFS compared to other locations (p-value = 0.03). Adjuvant postoperative radiotherapy had no significant impact on recurrence/progression rate or PFS. The extent of resection according to Simpson grade remains the most important prognostic factor associated with lower recurrence/progression rates and longer PFS in patients with atypical meningioma. The location of the tumours at the anterior or posterior fossa was an independent factor associated with improved PFS.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Adjuvant radiotherapy; Atypical meningioma; Meningioma; Surgery